Phonological Processing and Reading Skills In Children With Speech Disorders - Lubis, Yani; Dalimunthe, Herika; Nasution, Tuti Alawiyah Ramadani; Lubis, Nurul Hidayah; Lubis, Elfi Mawaddah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Youngsters who have difficulties pronouncing words also have difficulties comprehending and manipulating word sounds. Even if kids grow better at speaking as they age, this may still have an impact on how effectively they learn to read. The present study employs library research or literature review, a method that entails the collection of data and information from a variety of library resources, including reference books, prior research findings, articles, notes, and pertinent journals pertaining to the subject under investigation. To find out more about this, researchers consult earlier research and library books. Phonological awareness is the ability to recognize, manipulate, and break down sounds in words. Even before they can read, children need to have this talent. There are several methods to test it, including examining word constituents, like by looking at parts of words, such as the beginning sound and the rest of the word.